Evolution of the IgE and IgG repertoire to a comprehensive array of allergen molecules in the first decade of life. Issue 2 (9th October 2017) - Huang, X.; Tsilochristou, O.; Perna, S.; Hofmaier, S.; Cappella, A.; Bauer, C.‐P.; Hoffman, U.; Forster, J.; Zepp, F.; Schuster, A.; D'Amelio, R.; Wahn, U.; et al.
Abstract: Background: In early childhood, the allergen‐specific IgG repertoire is mainly directed to animal and vegetable food molecules and infrequently to airborne molecules. It is unknown whether this early pattern is maintained throughout childhood. Objective: To investigate the evolution of IgG and IgE responses to a broad panel of allergenic molecules from birth to age 10 years. Methods: We examined the sera collected between birth and age 10 years from participants in the German Multicentre Allergy Study, a birth cohort born in 1990. The IgE (cutoff ≥0.30 ISU) and IgG (cutoff ≥0.10 ISU) responses to 35 genuine allergenic molecules were measured with a multiplex microarray approach (ImmunoCAP ISAC™). Results: IgE responses were mostly directed against a restricted group of airborne molecules, with a sequence and prevalence hierarchy (Phl p 1> Bet v 1> Fel d 1> Phl p 5> Der p 2> Der p 1) largely maintained over time. Conversely, the IgG repertoire was much broader, starting with animal foodborne, then spreading to vegetable foodborne and finally to airborne molecules. A strong and persistent IgG response to a given airborne molecule almost invariably preceded or accompanied an IgE response to that molecule. Conclusions: The evolution of IgG and IgE responses throughout childhood differs widely at population level. IgG responses are mostly directed to animal food allergens, while IgE responses are dominated by airborne allergens. However, a strong IgG response almost invariably precedes or accompanies the appearance of IgE to the same molecule in specifically sensitized subjects.